2013
DOI: 10.1159/000342548
|View full text |Cite
|
Sign up to set email alerts
|

IGF-I in Human Growth: Lessons from Defects in the GH-IGF-I Axis

Abstract: The IGF system plays a critical role in all phases of human growth, including intrauterine, childhood and pubertal. The importance of IGF-I for both in utero as well as postnatal human growth is highlighted by rare human homozygous IGF1 mutations, which are characterized by intrauterine growth retardation (IUGR), microcephaly, mental retardation and severe postnatal growth failure. Clinical conditions of IGF-I resistance due to mutations in the IGF-I receptor (IGFIR) similarly lead to IUGR and postnatal growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
(56 reference statements)
0
15
0
Order By: Relevance
“…Also listed are some of the Functional Consequences (Box 4) of height variation for individuals, communities, and populations (Steckel, 2012). Detailed discussion of the categories and factors of Figure 1 are available in the literature (Eveleth and Tanner, 1991;Komlos and Baten, 1998;Bogin, 1999;Steckel, 2009;Kuzawa and Quinn, 2009;Blum et al, 2011;Muñoz-Hoyos et al, 2011;Dubois et al, 2012;Hermanussen, 2013;Hwa et al, 2013;Simeone and Alberti, 2014;McDade et al, 2016).…”
Section: -----------------------------------------mentioning
confidence: 99%
See 1 more Smart Citation
“…Also listed are some of the Functional Consequences (Box 4) of height variation for individuals, communities, and populations (Steckel, 2012). Detailed discussion of the categories and factors of Figure 1 are available in the literature (Eveleth and Tanner, 1991;Komlos and Baten, 1998;Bogin, 1999;Steckel, 2009;Kuzawa and Quinn, 2009;Blum et al, 2011;Muñoz-Hoyos et al, 2011;Dubois et al, 2012;Hermanussen, 2013;Hwa et al, 2013;Simeone and Alberti, 2014;McDade et al, 2016).…”
Section: -----------------------------------------mentioning
confidence: 99%
“…. Martin, 2012;Eveleth and Tanner, 1991;Hermanussen, 2013;Hwa, Fang, Derr, Fiegerlova, & Rosenfeld, 2013;Komlos and Baten, 1998;Kuzawa and Quinn, 2009;McDade, Georgiev, & Kuzawa 2016; Muñoz-Hoyos, Molina-Carballo, Augustin-Morales, Contreras-Chova, Naranjo-G omez, Justicia-Martínez, & Uberos, 2011;Simeone and Alberti, 2014;Steckel, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Neurotrophic factors, such as insulin-like growth factor 1 and its type 1 receptor (IGF-1R), are known to modulate the synaptic activity of dopamine and glutamate in the developing and adult nervous systems (Guevara-Aguirre, 1996; Mattson, 2008; Mattson, 1990; Pehar et al, 2010). Moreover, alterations in neural IGF-1 have been described in the cause and progression of several neuropsychiatric disorders associated with development, aging, degeneration and malformation of cytoskeletal proteins in neurons (Guevara-Aguirre, 1996; Hwa et al, 2013; Pehar et al, 2010). Additionally, other reports have shown that loss of neurotrophins, and associated receptors are pivotal to a compromised synaptic integrity, abnormal neurotransmitter signaling events and activation of inflammatory pathways in traumatic stress (Su et al, 2015; Finsterwald et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, several proteins and their coding regions in the genome have been identified that affect postnatal growth [4, 5]. The GH–IGF-I axis is involved in all phases of human growth, including intrauterine growth, childhood and pubertal development.…”
Section: Introductionmentioning
confidence: 99%
“…Laron syndrome and severe GH deficiency probably represent the 2 extreme ends of molecular defects covering the GH–IGF-I axis. Since the description of Laron syndrome, several conditions have been identified with a less severe phenotype, which make a biochemical continuum from GH deficiency towards GH insensitivity likely [5]. The prevalence for individuals with SPIGFD has been estimated to be about 1: 50.000.…”
Section: Introductionmentioning
confidence: 99%